Evaluation of the wear rates of eight different brands of artificial resin teeth - Assunção, Wirley G.; Barbosa, Débora B.; Goiato, Marcelo C.; Tabata, Lucas F.; G. Filho, Humberto (Brazilian Dental Science, 2010)
The wear of artificial resin teeth used in prosthetic rehabilitation treatment is of great concern to the dentist, since wear changes the occlusal vertical dimension (OVD) and may provoke cranio-mandibular disturbance, decrease masticatory efficiency, increase the discomfort for the patient and alter esthetics. Thus, one of the most important physical properties of artificial teeth is their abrasion resistance and the ability to maintain the occlusal relation of the patient stable. To evaluate the rates of wear of eight commercially available brands of artificial resin teeth, forty-eight samples were prepared from 8 different brands, totaling 8 groups each with six elements. The samples were evaluated by a gravimetric method, and analyzed by measuring the difference between the initial and final weights following the experiment. Obtained values were submitted to variance analysis and Tukey’s test (p